Do Migrant Remittances Reduce Poverty? Micro-Level Evidence from Punjab, Pakistan - Imran, Kashif; Devadason, Evelyn Shyamala; Cheong, Kee Cheok (Malaysian Economic Association, 2018)
This paper provides a poverty profile of households and then investigates the effects of international remittances on poverty incidence and severity in Punjab, Pakistan. Using cross-section data from the latest Multiple Indicator Cluster Survey for Punjab, the disaggregated analysis on the remittance-poverty nexus is examined by districts and urban-rural locales. From the poverty profile for migrant households with remittances and the counterfactual scenario of no remittances, the differences in the poverty reduction effect seem larger for poverty headcount than on the depth of poverty. The same trend holds for the urban-rural locales. This implies that remittances inflow were not really helpful for the poorest of the poor. The regression analysis further reveals that migrant remittances have significantly reduced the level and depth of poverty for households in all districts of Punjab, with the highest probability of being non-poor for rural households in the districts of South Punjab.